Improved adhesion, growth and maturation of vascular smooth muscle cells on polyethylene grafted with bioactive molecules and carbon particles - Parizek, Martin; Kasalkova, Nikola; Bacakova, Lucie; Slepicka, Petr; Lisa, Vera; Blazkova, Martina; Svorcik, Vaclav (International journal of molecular sciences, 2009)
High-density polyethylene (PE) foils were modified by an Ar(+) plasma discharge and subsequent grafting with biomolecules, namely glycine (Gly), polyethylene glycol (PEG), bovine serum albumin (BSA), colloidal carbon particles (C) or BSA and C (BSA + C). As revealed by atomic force microscopy (AFM), goniometry and Rutherford Backscattering Spectroscopy (RBS), the surface chemical structure and surface morphology of PE changed dramatically after plasma treatment. The contact angle decreased for the samples treated by plasma, mainly in relation to the formation of oxygen structures during plasma irradiation. A further decrease in the contact angle was obvious after glycine and PEG grafting. The increase in oxygen concentration after glycine and PEG grafting proved that the two molecules were chemically linked to the plasma-activated surface. Plasma treatment led to ablation of the PE surface layer, thus the surface morphology was changed and the surface roughness was increased. The materials were then seeded with vascular smooth muscle cells (VSMC) derived from rat aorta and incubated in a DMEM medium with fetal bovine serum. Generally, the cells adhered and grew better on modified rather than on unmodified PE samples. Immunofluorescence showed that focal adhesion plaques containing talin, vinculin and paxillin were most apparent in cells on PE grafted with PEG or BSA + C, and the fibres containing alpha-actin, beta-actin or SM1 and SM2 myosins were thicker, more numerous and more brightly stained in the cells on all modified PE samples than on pristine PE. An enzyme-linked immunosorbent assay (ELISA) revealed increased concentrations of focal adhesion proteins talin and vinculin and also a cytoskeletal protein beta-actin in cells on PE modified with BSA + C. A contractile protein alpha-actin was increased in cells on PE grafted with PEG or Gly. These results showed that PE activated with plasma and subsequently grafted with bioactive molecules and colloidal C particles, especially with PEG and BSA + C, promotes the adhesion, proliferation and phenotypic maturation of VSMC.
Keywords: kultivované buňky; Carbon; Muscle, Smooth, Vascular; Cells, Cultured; aktiny; Cell Proliferation; Polyethylene; Rats; aorta; kyslík; sérový albumin hovězí; Oxygen; plasma irradiation; polyethylen; Animals; proliferace buněk; glycin; tissue engineering and reconstruction; biocompatibility; buněčná adheze; svaly hladké cévní; Glycine; zvířata; Cattle; skot; mikroskopie atomárních sil; bioactivity; Actins; Aorta; krysa rodu Rattus; Microscopy, Atomic Force; polyethylenglykoly; Serum Albumin, Bovine; Cell Adhesion; Polyethylene Glycols; uhlík